Efficacy of Er:YAG Laser in Decontamination of Dental Implants: an in-vitro Study - AlMoharib, Hani. (2018)
Abstract: Aim: The primary aim of this prospective randomized controlled clinical trial was to compare the efficacy of biofilm removal from dental implant-like flat titanium surfaces by Erbium-doped yttrium-aluminum-garnet (Er:YAG) laser, titanium brush, and carbon fiber curette. The secondary aim was to evaluate the amount of residual live biofilm in the same treatment groups. Materials & Methods: Eight study subjects who fit the inclusion criteria were recruited in the study. A custom mouth appliance that holds 8 sand-blasted and acid etched titanium discs was fabricated for each subject. Subjects were asked to wear this appliance for 72 hours to allow for biofilm development on the discs. After retrieving the appliance, the discs were removed and randomized to one of four treatment groups: 1) Er:YAG laser, 2) titanium brush, 3) carbon fiber curette and 4) no treatment (control). The discs were stained with LIVE/DEAD BacLight dye and the residual biofilm was visualized under fluorescence microscopy. Quantification of residual biofilm was performed using imageJ analysis software and expressed as percentage surface area. Results: A total of 59 titanium discs were retrieved. The percentage of titanium disc area covered by biofilm was 74.03 ± 21.61%, 32.78 ± 24%, 11.80 ± 10.29% and 20.14 ± 19.15% in the control, Er:YAG, titanium brush and carbon fiber curette group, respectively (Mean ± SD). The biofilm-covered area significantly decreased in each of the 3 treatment groups when compared to the untreated control (p<0.008). Comparisons between the Er:YAG laser, titanium brush and carbon fiber curette treatment groups were not statistically significant. The percentage of titanium disc area covered by live biofilm for the control group (Mean ± SD: 33.56 ± 19.21), the Er:YAG group (Mean ± SD: 24.28 ± 16.31), the titanium brush group (Mean ± SD: 10.91 ± 9.86), the carbon fiber curette group (Mean ± SD: 19.68 ± 18.68). For residual live biofilm area percentage, no statistically significant difference was found between the groups. Conclusions: Er:YAG laser is an effective method in reducing the bacterial biofilm on titanium discs. However, on a threadless titanium surface Er:YAG laser did not exhibit significantly greater efficacy in biofilm removal compared to commonly used titanium brushes or carbon fiber curettes.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Periodontology.; Advisor: Robert Gyurko.; Committee: Bjorn Steffensen, Driss Zoukhri, and Matthew Finkelman.; Keyword: Dentistry.